2006
DOI: 10.1111/j.1365-2818.2006.01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and electrical properties of diborides modified by rapid thermal annealing

Abstract: SummaryDiborides of Ti, Hf and Zr are thermally, mechanically and chemically stable with good thermal and electrical conductivity. We tested their properties in front-end processes used in Si integrated circuits (IC). Films were deposited by e-beam evaporation either on Si, for the formation of contacts to the source/drain (S/D) regions, or on Si oxides, for the formation of metal gates in p-type metal-oxide-semiconductor (PMOS) transistors. We focused on their crystallization caused by rapid thermal processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…This clearly indicates that there is no evidence of superconductivity in this compound. Of course, this conclusion matches to direct calculation of transition temperature according Formula (5).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This clearly indicates that there is no evidence of superconductivity in this compound. Of course, this conclusion matches to direct calculation of transition temperature according Formula (5).…”
Section: Discussionmentioning
confidence: 89%
“…Presently, a number of experimental studies exists dealing with the physical properties of HfB 2 , such as thermal and electrical properties [4][5][6][7], mechanical [8], and elastic properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…The stoichiometric diborides are thermally stable with very high melting temperatures, well in excess of those of both Ni and Pt. 21,22 They also exhibit good corrosion resistance but are susceptible to oxidation during thermal processing. 21,22 This may be countered by depositing an overlayer of a metal such as Au in the same deposition chamber.…”
Section: Introductionmentioning
confidence: 99%
“…18 Typical Schottky metallizations for AlGaN/GaN HEMTs are based on Pt/Au or Ni/Au, with Au included to reduce the sheet resistance of the contact and to prevent oxidation of the other metal. [20][21][22][23][24][25][26][27][28][29][30][31] Other potentially more thermally stable metallization schemes based on W or WSi x have been reported. [13][14][15][16]20 These exhibit low barrier heights around 0.4-0.5 eV.…”
Section: Introductionmentioning
confidence: 99%
“…It has been showed that annealing of amorphous ZrB2 films, deposited by e-beam evaporation, decreases their resistivity due to grain growth [65]. Annealing of sputtered epitaxial ZrB2 films should be investigated to see if the column width increases and the resistivity decreases.…”
Section: Future Outlookmentioning
confidence: 99%